The floor finishes category impact for indoor sports centre - Masnan, Izhar; Yaman, Rostam; Ismail, Farrah Zuhaira; Ahmad, Noraini (College of Built Environment (CBE), 2024)
According to Fobo flooring system, the sports floor surface is possibly the most significant aspect of equipment in any sporting facility. Sports flooring is not one specific thing but rather a variety of floor coverings or construction methods using a range of materials for a range of athletic uses. Based from Ecotile Flooring sport facilities need a durable, functional, and aesthetically pleasing floor that is safe. It can be challenging to find an impact-resistant floor that satisfies all the requirements given the variety of activities that take place in the facilities. This research aims to ascertain the floor finish category impact for sports centre. The objectives were to determine the floor finishes category for interior sports centre design and to examine the impact of flooring category in sport centre that influence the user performance. Site observation was done in two different location of the selected sport centre and a questionnaire was also distributed there. The results indicate that most of the respondents agreed to poor sports facility flooring can endanger users and the type of floor finish used in a sports centre can affect the performance of users during they are doing sport activities. In sports, fitness, and recreation applications, one size does not fit all when it comes to flooring. Athletic flooring must do more than look good at a good price point. These surfaces ought to safeguard sportsmen and fitness enthusiasts while enhancing performance. Engineered performance surfaces can be advantageous for ergonomics, acoustics, and safety.